Hydroponic Training to Improve Community Living Standards in Densely Populated and Weak Economies - Bob Foster; Fitriani Reyta; Muhamad Deni Johansyah (Budapest International Research and Critics University, 2021)
Simple hydroponic technology plays a role in increasing human capacity and capacity to deal with the impacts of climate change and contribute to sustainable development. Dealing with the impacts of climate change means reducing significantly or eliminating negative effects on society and the natural environment, this activity can be started through simple things such as reforesting the immediate environment in the community. The principle of sustainable development is an important guide to ensure that the use of simple technologies such as hydroponics to reduce climate change by recycling materials also has an impact on increasing the ability of future generations to meet their own needs. I Green Project, We Grow Communityis a community service initiated by LPPM Universitas Informatics and Bisnis Indonesia in collaboration with the International Student Organization AIESEC focuses on the role of academics in mitigating climate change by adopting actions to mitigate the impacts of climate change. Because climate and environment are interrelated, this community service also considers the role of hydroponics as greening the environment in helping individuals understand the environment around them, which is a prerequisite for overcoming the problem of climate change. Pengabdian located in Baranang Siang, Bandung City, West Java, 2018 has provided an understanding of the steps needed to reduce climate change, including several policy issues that need to be addressed, changing environmental conditions to be greener and activating community participation to have additional income from the program. Hydroponics so that people with weak economies are more helped to be independent. This program is implemented for 1 month in August with the number of community members as executors of 30 (thirty) people.